Motivations for Religious Content Selection among Nairobi Youth (African Multidisciplinary Journal of Research, 2025)
Radio evangelization continues to play a significant role in shaping religious experiences in Kenya, but its effectiveness depends largely on whether its content resonates with the needs and motivations of listeners. This paper examines the motivations behind the selection of religious radio content among youth in Nairobi County. Drawing on the uses and gratifications theory, which is driven by inherent needs to seek specific information to satisfy specific needs, the study applies a descriptive design and mixed-methods approach for data collection. Data were collected through structured questionnaires, complemented by two focus group discussions and semi-structured interviews with radio producers and presenters. Quantitative data were analysed using SPSS, while qualitative data were thematically examined with NVivo.  Findings revealed that youth select religious radio content primarily for spiritual inspiration and reinforcement of faith (87%), emotional uplift through gospel music (81%), and practical guidance on contemporary life challenges such as relationships and employment (76%). Social and integrative needs also emerged, with 68% reporting that radio provided a sense of belonging to the wider faith community. Entertainment value, especially through culturally relevant gospel music and youth-friendly segments, was another key motivator. However, barriers such as limited interactivity, language exclusivity, and perceived repetitiveness of content reduced engagement for some listeners.  By contextualizing broadcasts to address real-life issues, offering interactive platforms, and diversifying language and content, religious radio can sustain youth interest and participation in religious life. This paper contributes to practical strategies for faith-based broadcasters seeking to deepen youth engagement in Nairobi’s rapidly evolving media environment.